ANALYSIS OF MYCOPLASMA GALLISEPTICUM INFECTION FACTORS IN COMMERCIAL LAYER CHICKEN FARM USING ANALYTICAL HIERARCHY PROCESS - Diyantoro, Diyantoro; Pribadi, Eko Sugeng (Journal of Vocational Health Studies, 2017)
Background: Mycoplasma galliseptium (MG) is a pathogenic microbial often found in poultry farm industry. In Indonesia there are rarely data of MG research. There are some factors increased the risk of MG infection. Purpose: This research aimed to determine the factors involved in the transmission of MG in commercial layer chicken farm. Method: This was a descriptive research with the data was collected from pairwise comparison questionnaire distributed to poultry expert. The Data was analyzed using Analytical Hierarchy Process (AHP) supported by computer programme "Expert Choice”. Result: The results showed that risk value of rearing management (0.425), health management (0.312), feed management (0.088), and biosecurity of  farm (0.175) to the transmission of MG. The results of AHP analysis to the risk factor variables of MG infection in commercial layer chicken farm showed that the highest risk value of MG infection was the number of bird in house (0.277), followed by antibiotic administration (0.276), while the other variables only have risk value under 0.100. Conclusion: The highest risk value of MG infection was rearing management factor especially on the variable of the population number of poultry in house.